Evidence that Calcium Regulates Platelet Function - Detwiler, Thomas C; Charo, Israel F; Feinman, Richard D (Thrombosis and Haemostasis, 1978)
It is generally believed that calcium ions play a key role in regulation of platelet function.This is based on 3 types of evidence.1. Analogies with other cells. Calcium ions are known to trigger secretion and contraction in many cells, possibly reflecting a general role for calcium in all secretion and contraction.2. Indirect evidence. Platelet aggregation and secretion are induced by divalent cation ionophores. The response to the ionophore A23187 is identical to that induced by other potent stimuli.3. Direct evidence. Platelet activation can be blocked by drugs (e. g. certain local anesthetics) that block release of calcium ions from sarcoplasmic reticulum; the inhibition can be overcome by addition of extracellular calcium in the presence of a calcium ionophore. While this does not constitute definitive proof, the central role for calcium ions remains an attractive hypothesis that justifies attempts to further define calcium pools and fluxes in platelets.